Alchemical poetics in seventeenth-century women's writing - Allan, KF (2023)
This thesis explores how four female poets—Aemilia Lanyer (1569-1645), Hester Pulter (1607-1678), Katherine Philips (1632-1664), and Margaret Cavendish (1623-1673)—conceptualise poetry as an alchemy of the mind that nonetheless has real, practical implications for themselves and for their readers. The ‘alchemical poetics’ of these women writers thus exhibit a lively interest in, and radical transformation of, alchemical thought that grapples variously with the saving of souls, healing of the body, and transmutation of matter. More crucially, I contend that this grouping of women writers is actively participating in the evolution of alchemical thought through poetry.